Life history, habits and phylogenetic relationships of Ithycerus noveboracensis (Forster), (New York weevil) (Coleoptera: Curculionoidea) - Sanborne, Paul Michael (My University, 1979)
Larvae of Ithycerus are described for the first time. Ten instars are identified with the possibility of more to be found. The pupa remains unknown. Spiracular air tubes and orifices show allometric growth and this, combined with body and head capsule measurements, is used to separate instars. Female and male reproductive systems are described. Females have two ovarioles per ovary. Adult and larval stages have four cryptonephric Malphigian tubules in the digestive tract. Adult and larval nervous systems appear to be primitive in possessing long connectives between ganglia. The first instar larva of Arrhenodes minutus (Drury) is described for the first time. The first illustrations of Antliarrhinus larvae are included. Ithycerus noveboracensis (Forster) has a two year life cycle at least and possibly three. Adults do not overwinter. Three families of woody plants are associated with Ithycerus, the Betulaceae, Juglandaceae and Fagaceae, with a preference for species of Fagaceae. Adults are also occasionally found on introduced fruit trees (Rosaceae). There is no obvious courtship in Ithycerus. Oviposit!on takes place in soil; eggs are laid singly and covered with fecal matter. The larvae feed on the vascular cambium of the roots of host plants. Several grooming movements and modes new for Coleoptera were discovered in Ithycerus and include bilateral fore-mid leg rub, mid-hindleg rub (third mode), bilateral hindleg rub (third mode), simultaneous fore-midleg rub (one side), mid-hindleg rub (other side) and flagellum extend. Female A. minutus rapidly flutter the tips of their antennae against the tip of the rostrum to dislodge wood particles trapped there while drilling egg holes. Evidence is presented for the possibility of evolution of three forms of Ithycerus in pleistocene refugia. The family Ithyceridae is maintained on the basis of new characters, primarily larval. The family is viewed as the most primitive of the four apionid-like families recognized in this study, the others being Brenthidae, Antiiarrhinidae status nov. and Apionidae. The family Antiiarrhinidae is placed near Apionidae. Adult and larval ventral nervous systems are discussed in light of their possible value as phylogenetic indicators. An evolutionary sequence is postulated for the numbers and positions of sensilla on the labra of larvae.
Keywords: New York weevil